Features of developing corporate social responsibility strategies of foreign brands (The Journal of Psychology and Sociology, 2022)
The article discusses the features of the development of corporate social responsibility strategies of foreign brands. The purpose of the strategy is to manage projects and processes in the field of corporate social responsibility and define the basic principles and priorities of the business. The strategy ensures the sustainable development and improvement of the efficiency of corporate socially responsible business using the norms enshrined in international standards. Our main task is to identify strategic directions for the formation of social responsibility of Kazakhstan business in modern conditions. In this regard, a comparative analysis and results of the implementation of corporate social responsibility strategies of foreign brands are given. Here are the studies of Starbucks, H&M and IKEA based on literature, including information collected from the analysis of scientific publications and scientific articles. These comparative analyzes and results can serve as an example of the formation of social responsibility strategies of Kazakh business. In the future, serious sociological studies of strategies of corporate social responsibility of foreign brands operating in Kazakhstan are necessary.It is important to determine the strategic directions of the development of social responsibility of the Kazakh business by means of comparative sociological studies. The fact is that the environment, opportunities and framework of business functioning are changing now, and time requires continuous changes. In principle, the strategy should be built with an emphasis not only on the interests and success of the business, but on the interests of the collective, more precisely, society. Keywords: social responsibility of Business, Corporate Social Responsibility, brand, strategy, EFQM.